Applied medical image processing : a basic course - Birkfellner, Wolfgang (Boca Raton, Fl. : CRC Press, 2014)
'This widely used, classroom-tested text continues to be an ideal introduction to image processing in medicine. Updated and expanded, this edition gives more attention to the subject of color space and includes more examples from radiology, internal medicine, surgery, and radiation therapy. The book addresses problems with handling voxels, 3D data sets, spatial transforms in three dimensions, and data fusion. It shows how to visualize large data sets from modern CT systems in radiology, manufacture patient-specific prostheses for orthopedic surgery, plan dose distributions in radiation oncology, incorporate multimodal image data for therapy monitoring in internal medicine, and perform computer-aided neurosurgical interventions. Examples are given throughout and an accompanying CD-ROM includes programming techniques in MATLAB'--Provided by publisher.
Book is accompanied by one computer optical discs entitled' Applied medical image processing : a basic course' bearing the same call number and available at Unit Koleksi Media.
Includes bibliographical references and index.
Keywords: Diagnostic imaging; Diagnostic imaging -- Digital techniques; Image analysis